FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN DISTRESS EMOSIONAL PADA CAREGIVER PEREMPUAN DENGAN ANGGOTA KELUARGA YANG MENGALAMI GANGGUAN JIWA - Ira Erwina; Reni Prima Gusty; Monalisa - (Fakultas Keperawatan Universitas Andalas, 2012)
Caring for mental patients can be done by families and health professionals. The family is the closest to patients with mental disorders, referred as caregiver. Caregiver always give support for patient care. Caring for patients with mental disorders will make caregivers vulnerable to emotional problems such as anxiety, depression and worries. The purpose of this study was to determine the emotional distress experienced by female caregiver and the characteristics and its relationship with mental patients. Design of this research is analytic survey with purposive sampling technique. The total sample of 86 respondents, data were collected using questionnaires. The results of the data obtained and tested using correlation analysis. The result is women caregivers for experiencing emotional distress is 7.73 (77.3%), and there is a relationship between the family situation (caregiver relationship and supervision) to emotional distress, and there is no relationship between the characteristics of caregivers and the characteristics of mental disorder patients with emotional distress. Advised the caregiver to seek information and to improve the ability to solve problems.